Phase and texture analysis of a hydride blister in a Zr–2.5%Nb tube by synchrotron X-ray diffraction - Vicente Alvarez, Miguel Angel (2011)
This paper presents a detailed phase and texture study within and around a hydride blister grown on the surface of a Zr–2.5%Nb pressure tube. The analysis is based on synchrotron X-ray diffraction experiments using an 80 keV photon beam and a high-speed area detector placed in transmission geometry. It was found that the blister is composed of two main phases, a-Zr and d-ZrH, with a composition which changes locally across the blister. No location within the blister presents pure d zirconium hydride, with a maximum of 80% for the volume fraction of d hydride at the center of the blister. The texture observed for both phases in the original pressure tuberemains essentially unaltered across the hydride blister. A detailed analysis of this texture using well-known parent–precipitate relationships shows that some selective precipitation occurs at a-Zr grains with their c-axis under a tensile stress, and on grains with grain boundaries favorably aligned for hydride nucleation.